STUDI FENOMENOLOGI PENGALAMAN KELUARGA SEBAGAI PRIMARY CAREGIVER DALAM MERAWAT LANSIA DENGAN DEMENSIA DI KABUPATEN JOMBANG - Muhammad Rosyidul‘Ibad* Ahsan** Retno Lestari*** (Universitas Muhammadiyah Jember, 2016)
Primary family caregiver is the closest person whose main function is thecare of elderly dementia at home. They not only take care of elderly dementia alone,but also they have other roles and functions within the family. Primary familycaregivers often feel a negative impact such as psychological, social, and financialdisorders with the elderly dementia at home. Their dillemas conditions andconsequences as a result of caring for elderly people with dementia at home developresearcher’s spirit to explore the experience of the family as the primary caregiverin caring for the elderly with dementia in Jombang. The researchers used aqualitative design with interpretive phenomenological approach, the retrieval ofdata using in-depth interviews with semi-structured interview guide and field notesinvolve 5 participants. This research resulted in four themes (1) an overview of theprimary family caregivers to elderly dementia (2) the condition of elderly dementia(3) consequences of elderly dementia at home (4) act of primary family caregiver.Primary family caregiver get an overview from the ability to think and feel deeply,it is important to establish a sense of empathy as a foundation in performingmaintenance actions despite obstacles during the treatment process. Negative effectthat primary family caregiver receives makes them vulnerable to the risk of mentaldisorders. Caring for elderly dementia is difficult to do if only rely on experiencealone, therefore primary care giver need for strength.